My darling husband - Belle, Kimberly (Park Row Books, 2021)
"Jade and Cam Lasky are by all accounts a happily married couple with two adorable kids, a spacious home and a rapidly growing restaurant business. But their world is tipped upside down when Jade is confronted by a masked home invader. As Cam scrambles to gather the ransom money, Jade starts to wonder if they're as financially secure as their lifestyle suggests, and what other secrets her husband is keeping from her"--